Topographical and Functional Changes in the City of Lodose during the Middle Ages - Carlsson, Kristina (Hikuin, 1998)
Lodose lay in west central Sweden, close to the Danish and Norwegian borders and the Swedes had to use a narrow corridor to reach the sea for trading along the North Sea coast. It was built on the east bank of the river Gota Alv, an important transport route vital for the foundation of this merchant town and also the border between Sweden and Norway.